Effect of Source and Level of Maternal Vitamin D on Carryover to Newly Hatched Chicks - Coto, Cesar; Cerate, S.; Wang, Z.; Yan, F.; Waldroup, P.W. (International Journal of Poultry Science, 2010)
A study was conducted to evaluate the carryover effect of maternal vitamin D level and source on performance and bone development of the progeny. Breeder hens were fed a vitamin D deficient diet for two months to deplete stores. After this period, experimental diets in a factorial arrangement were fed to the hens with five levels of cholecalciferol (0, 300, 600, 1200 and 2400 IU/kg) and two levels of 25OHD3 (HyD) (0 and 68 μg/kg) for a total of 10 treatments. At the end of two months on the experimental diets two sets of eggs were hatched. The progeny obtained were placed in battery brooders to 21 days by maternal diet and received a common diet. The first hatch received a diet with no vitamin D supplement whereas the second hatch received a diet with the same nutrient composition but containing 5500 IU/kg of cholecalciferol. The first set of birds responded to the maternal diet supplementation of vitamin D mostly during the first week post hatch with no clear pattern in later stages. The progeny receiving 5500 IU/kg of vitamin D in the diet responded to the maternal vitamin D supplementation even at 21 days and in a clearer trend. Feed conversion and body weight improved as the cholecalciferol level increased and with the inclusion of HyD in the maternal diet. The response when HyD was added was more noticeable at low levels of cholecalciferol supplementation with no difference at higher levels in the hen’s diet. Bone development of the progeny was improved with the addition of HyD in the maternal diet; this response was not influenced by increasing levels of cholecalciferol in the breeder diet. This study confirms the importance of the maternal vitamin D carryover for an adequate development of the progeny. Certainly, the vitamin D carryover effect did not overcome the effect of supplementing vitamin D directly in the progeny’s diet but it was capable of improving the performance of the progeny even three weeks post-hatch when a high level of cholecalciferol (5500 IU/kg) was present in the diet of the progeny. A carryover effect of HyD when added to the maternal diet was observed in this study, thus the feasibility of using the metabolite to supply vitamin D to the developing embryo was confirmed.